1998
DOI: 10.1111/j.1439-0264.1998.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Bovine Palatine and Pharyngeal Tonsils at 21, 60 and 300 Days of Age

Abstract: An immunohistochemical study was performed on three groups of young cattle (21, 60 and 300 days of age). Tonsils (palatine and pharyngeal) and mucosae (nasal and oral) were removed. Eight monoclonal antibodies (specific for CD3, CD2, CD4, CD8, WC1, cell-surface IgM, cell-surface IgG and MHC class II molecules) and an avidin/biotin complex method on frozen sections were used. The immunological cytoarchitecture of bovine tonsils is similar to that of human tonsils. Nevertheless, these lymphoid tissues are not fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Types and numbers of lymphocyte subsets observed in the reticular epithelium of the present study are similar to those described previously for the bovine pharyngeal tonsil (Schuh and Oliphant, 1992;Manesse et al, 1998), bovine palatine tonsil (Palmer et al, 2009) and ovine tonsils (Breugelmans et al, 2011). Pharyngeal tonsilar reticular epithelium contained numerous CD4þ T-lymphocytes and B-B7þ B-lymphocytes.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Types and numbers of lymphocyte subsets observed in the reticular epithelium of the present study are similar to those described previously for the bovine pharyngeal tonsil (Schuh and Oliphant, 1992;Manesse et al, 1998), bovine palatine tonsil (Palmer et al, 2009) and ovine tonsils (Breugelmans et al, 2011). Pharyngeal tonsilar reticular epithelium contained numerous CD4þ T-lymphocytes and B-B7þ B-lymphocytes.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast to the present study, as well as human lymphoepithelium where CD4þ T-lymphocytes outnumber CD8þ T-lymphocytes (Gebert and Pabst, 1999), previous studies have identified CD8þ T-lymphocytes as the most numerous subtype in tonsilar reticular epithelium (Manesse et al, 1998). Differences between this study and the present one could be due to the use of different anti-CD8 antibodies that recognized different subpopulations of CD8þ cells.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In the bovine, a moderate amount of lymphoid tissue is present in Waldeyer's ring ( [78,118], Fig. 2A).…”
Section: Composition Of the Waldeyer's Ringmentioning
confidence: 99%
“…The palatine tonsils are also not fully developed at birth, but differentiate further after antigen contact [78]. In 3 week old calves, the palatine tonsils are still unorganized, but they are well organized in 2 month old calves [78].…”
Section: Palatine Tonsilsmentioning
confidence: 99%